Proceedings of the Forty-Eighth Annual ACM Symposium on Theory of Computing 2016
DOI: 10.1145/2897518.2897570
|View full text |Cite
|
Sign up to set email alerts
|

A lower bound for the distributed Lovász local lemma

Abstract: We show that any randomised Monte Carlo distributed algorithm for the Lovász local lemma requires Ω(log log n) communication rounds, assuming that it finds a correct assignment with high probability. Our result holds even in the special case of d = O(1), where d is the maximum degree of the dependency graph. By prior work, there are distributed algorithms for the Lovász local lemma with a running time of O(log n) rounds in bounded-degree graphs, and the best lower bound before our work was Ω(log * n) rounds [C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
155
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(157 citation statements)
references
References 46 publications
1
155
0
1
Order By: Relevance
“…We extend Brandt et al's [11] randomized lower bound as follows: on degree-∆ graphs, ∆-coloring takes Ω(log ∆ log n) time in RandLOCAL and Ω(log ∆ n) time in DetLOCAL. The hard graphs in this lower bound have girth Ω(log ∆ n), so by the indistinguishability principle, these lower bounds also apply to ∆-coloring trees.…”
Section: New Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We extend Brandt et al's [11] randomized lower bound as follows: on degree-∆ graphs, ∆-coloring takes Ω(log ∆ log n) time in RandLOCAL and Ω(log ∆ n) time in DetLOCAL. The hard graphs in this lower bound have girth Ω(log ∆ n), so by the indistinguishability principle, these lower bounds also apply to ∆-coloring trees.…”
Section: New Resultsmentioning
confidence: 93%
“…On the upper bound side, Barenboim and Elkin [3] showed that for ∆ ≥ 3, ∆-coloring trees takes O(log ∆ n + log * n) time in DetLOCAL. We give an elementary proof that for ∆ ≥ 55, ∆-coloring trees can be done in O(log ∆ log n + log * n) time in RandLOCAL, matching Brandt et al's [11] lower bound up to the log * n. A more complicated algorithm for ∆-coloring trees could be derived from [29], for ∆ > ∆ 0 and some very large constant 4 Linial [24] actually only used the existence of ∆-regular graphs with high girth and chromatic number Ω( √ ∆). See [8] for constructions with chromatic number Ω(∆/ log ∆).…”
Section: New Resultsmentioning
confidence: 99%
“…This domain of distributed computing is extremely active and productive this last decade, analyzing a large variety of network problems in the so-called LOCAL model [37], capturing the ability to solve task locally in networks 1 . We refer to [4,5,8,13,18,20,21,24,42] for a non exhaustive list of achievements in context. However, all these achievements were based on an operational approach, using sophisticated algorithmic techniques and tools solely from graph theory.…”
Section: Related Workmentioning
confidence: 99%
“…However, all these achievements were based on an operational approach, using sophisticated algorithmic techniques and tools solely from graph theory. Similarly, the existing lower bounds on the round-complexity of tasks in the LOCAL model [32,35,8,23,3] were obtained using graph theoretical arguments only. The question of whether adopting a higher dimensional approach by using topology would help in the context of local computing, be it for a better conceptual understanding of the algorithms, or providing stronger technical tools for lower bounds, is, to our knowledge, entirely open.…”
Section: Related Workmentioning
confidence: 99%
“…Unfortunately, this approach is unlikely to lead to an O(log * n)-time algorithm; LLL is known to be a hard problem for a wide range of parameters [6].…”
Section: Prior Work Related To Partial Coloringsmentioning
confidence: 99%